Promoting Critical Thinking in Speaking Classes Using the Think-Pair-Share Technique - Sriyanda, Ricky; Priyana, Joko (Universitas Pendidikan Mandalika, 2024)
This study aimed to assess the effectiveness of the Think-Pair-Share (TPS) technique in enhancing students' critical thinking skills and to explore students' perceptions of its application in speaking classes. Using a Classroom Action Research (CAR) design based on Kurt Lewin's model, the study followed the steps of planning, acting, observing, and reflecting. The research was conducted with 30 second-grade students (12 male and 18 female) from SMAN, Aceh, Indonesia, in the 2023/2024 academic year, selected through purposive sampling. Data collection methods included classroom observations, questionnaires, and student interviews, with the analysis carried out using descriptive and qualitative statistics. The findings indicated a significant improvement in students' critical thinking skills, as shown by the increase in performance from Cycle 1 (66.6%) to Cycle 2 (70%). Moreover, the results of the questionnaires demonstrated that students responded positively to the TPS technique. Therefore, the study concludes that the TPS technique effectively promotes critical thinking skills in speaking classes, offering cognitive and engagement benefits.